2017
DOI: 10.1038/srep42332
|View full text |Cite
|
Sign up to set email alerts
|

Peptoids successfully inhibit the growth of gram negative E. coli causing substantial membrane damage

Abstract: Peptoids are an alternative approach to antimicrobial peptides that offer higher stability towards enzymatic degradation. It is essential when developing new types of peptoids, that mimic the function of antimicrobial peptides, to understand their mechanism of action. Few studies on the specific mechanism of action of antimicrobial peptoids have been described in the literature, despite the plethora of studies on the mode of action of antimicrobial peptides. Here, we investigate the mechanism of action of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 57 publications
2
69
0
Order By: Relevance
“…Preliminary studies had demonstrated that the peptoids GN‐2, GN‐2‐ N lys 1‐4 N trp 5‐8 and GN‐2‐ N pm 9 were valid antimicrobials (Table and Figure ), as they successfully inhibited the growth of E. coli by causing substantial membrane damage . However, as stated before, the peptide GN‐2 and the peptoid GN‐2 are not exactly analogues .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Preliminary studies had demonstrated that the peptoids GN‐2, GN‐2‐ N lys 1‐4 N trp 5‐8 and GN‐2‐ N pm 9 were valid antimicrobials (Table and Figure ), as they successfully inhibited the growth of E. coli by causing substantial membrane damage . However, as stated before, the peptide GN‐2 and the peptoid GN‐2 are not exactly analogues .…”
Section: Resultsmentioning
confidence: 89%
“…This study investigated the E. coli antibiofilm properties of peptide and peptoid variants modeled upon the synthetic peptide GN‐2, previously reported as a successful antimicrobial agent within a cohort of peptides generated through a QSAR‐based in silico approach . Preliminary studies reported the ability of peptoids GN‐2‐ N lys 1‐4 N trp 5‐8 and GN‐2‐ N pm 9 (Figure ) to inhibit the growth of E. coli , by disrupting its membrane integrity; however, their activity against E. coli biofilms was not investigated. In addition, a new set of peptide variants of these successful peptoids was synthetized to assess whether the antimicrobial potential was maintained in the transition from peptoid to peptide and to further clarify the antibacterial effects of lysine to arginine and phenylalanine to isoleucine substitutions in the sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The TiO 2 crystallized glass generates surface electron (e − ) and hole (h + ) which results in the peroxidation of cell wall membranes . Degradation of the cell wall alters the selective permeability of cell membrane and increases the pressure inside the cell which leads to cytolysis . ROS produced due to microelectrolysis of water molecules in the system enters into cells and increases the oxidative stress inside the cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are several mechanisms of membrane disruption in bacteria described for AMPs including barrel‐stave, carpet‐like, and formation of toroidal pores, yet none of them have been confirmed for peptoid substituents. Membrane damaging effect is suggested to be the primary mode of action by peptoids, while the potential intracellular targeting of ATP efflux, ribosome aggregation, enzymatic and mitochondrial activity, as well as nucleic acid synthesis, might be also involved. Peptoid amphipathic topology allows for electrostatic binding toward the lipid phosphate groups, implicated in membrane depolarization .…”
Section: Membrane‐active Peptoids: Advanced Peptide Biomimicrymentioning
confidence: 99%